Finding of Hyperostosis Frontalis Interna During the Autopsy Procedure: Forensic Issues. Issue 6 (4th June 2019) - Bascou, Agathe; Savall, Frederic; Vergnault, Marion; Montoriol, Romain; Guilbeau‐Frugier, Céline; Maupoint, Estelle; El Khal, Mohamed Chérif; Telmon, Norbert
Abstract: Hyperostosis frontalis interna is a common phenomenon, which may have been overrated in its significance in the past, and may, currently be underrated in its significance. We present three cases of hyperostosis frontalis interna found during medicolegal autopsies and discuss their forensic considerations. The patients were all middle‐aged women with metabolic and endocrine manifestations and psychiatric ailments; thickening of the inner table of the frontal bone of the skull was found during each autopsy. We describe the relationship between hyperostosis frontalis interna, metabolic manifestations, and neuropsychiatric symptoms as part of Morgagni‐Stewart‐Morel syndrome. There is still considerable disagreement in the scientific community as to whether this syndrome is a clinical entity. Nonetheless, awareness of Morgagni‐Stewart‐Morel syndrome can be of help in understanding the circumstances surrounding death. In some other cases, hyperostosis frontalis interna could be used by forensic pathologists as criteria for sexing and aging a skeleton.